ON THE FRONTIER OF RISK: THE RIGHT TO CARE AND THE THIRD SECTOR - Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2025)
This work’s general objective was to analyze the evolution of State civil liability in Brazil, focusing on the Administrative Alea as the culmination of this journey. The methodology used was bibliographic and documentary research, with a dogmatic and historical approach, examining doctrine, legislation (especially Law No. 14,133/2021), and the jurisprudence of the TCU and STJ. The content ranges from the dogma of state irresponsibility to the Theory of Unforeseeability and its practical application. The research shows that the Administrative Alea is a mechanism of justice that protects the private party from abnormal sacrifices caused by lawful acts of the State. The conclusions emphasize that the institute, in dialogue with the risk matrix and the rigor of the courts, ensures that the legal certainty and balance of Administrative Contracts are preserved. The analysis in Comparative Law reveals that the search for equity in the relations between the State and the private sector is a universal theme. The work reinforces the Administrative Alea as essential for a State guided by good faith and justice.